High performance MnO2 nanoflower supercapacitor electrode by electrochemical recycling of spent batteries. Issue 11 (1st August 2017) - Ali, Gomaa A.M.; Yusoff, Mashitah M.; Shaaban, Essam R.; Chong, Kwok Feng
Abstract: MnO2 nanoflower is prepared by electrochemical conversion of Mn3 O4 obtained by heat treatment of spent zinc‒carbon batteries cathode powder. The heat treated and converted powders were characterized by TGA, XRD, FTIR, FESEM and TEM techniques. XRD analyses show formation of Mn3 O4 and MnO2 phases for the heat treated and converted powders, respectively. FESEM images indicate the formation of porous nanoflower structure of MnO2, while, condensed aggregated particles are obtained for Mn3 O4 . The energy band gap of MnO2 is obtained from UV‒Vis spectra to be 2.4 eV. The electrochemical properties are investigated using cyclic voltammetry, galvanostatic charge‒discharge and electrochemical impedance techniques using three-electrode system. The specific capacitance of MnO2 nanoflower (309 F g −1 at 0.1 A g −1 ) is around six times higher than those obtained from the heat treated one (54 F g −1 at 0.1 A g −1 ). Moreover, it has high capacitance retention up to 93% over 1650 cycles. Impedance spectra of MnO2 nanoflower show very small resistances and high electrochemical active surface area (340 m 2  g −1 ). The present work demonstrates a novel electrochemical approach to recycle spent zinc-carbon batteries into high value supercapacitor electrode. Graphical abstract: Highlights: MnO2 nanoflower is obtained by electrochemical cycling of heat treated zinc‒carbon battery cathode powder. MnO2 nanoflower shows high specific capacitance of 309 F g −1 at 0.1 A g −1 in 1 M Na2 SO4 . MnO2 nanoflower has high capacitance retention of 93% over 1650 charge‒discharge cycles. MnO2 nanoflower shows small resistance and high electrochemical active specific surface area.